Enhancing PKBM Institutional Governance: A Strategic Model for Strengthening Managerial Competence - Oong Komar; Cucu Sukmana; Budi Setiawan (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This research describes the governance of managers in organizing programs in non-formal education units at Community Learning Activity Center (PKBM) of Al Insan Cikeusi Village Darmaraja District Sumedang Regency. Therefore, this study aims to initiate alternative solutions to the problem by searching and finding a product model of PKBM institutional governance in improving their competence. Methodology: The research design uses a qualitative descriptive approach. Data collection using interview techniques, observation, and documentation. Data analysis as an interactive model. Main Findings: The expected research results reveal the design of the PKBM Institution Governance model in improving the competence of PKBM Al Insan managers. The elements of the educational process are very influential on the course of the implementation process, these elements are the manager as the subject of program implementation, the subject being guided (students / learning citizens), the person who guides (educators / tutors), the interaction between students and educators. Likewise, governance, approaches, strategies and techniques in organizing programs are arranged into a unified system that makes more use of environmental conditions. Programs in non-formal education units have met the level of community needs for the importance of education. Novelty/Originality of this study: The output in this study created a product model of PKBM Institution Governance, national articles, HKI, mass media and governance guidelines and teaching materials for the PKBM Institution governance model.